2021
DOI: 10.3389/feart.2021.704901
|View full text |Cite
|
Sign up to set email alerts
|

Soil Freeze-Thaw and Water Transport Characteristics Under Different Vegetation Types in Seasonal Freeze-Thaw Areas of the Loess Plateau

Abstract: In the arid and semi-arid regions of the Loess Plateau, seasonal freezing and thawing influence soil water movement, and water movement directly influences vegetation growth. However, currently, research with regard to freezing and thawing processes under various vegetation types and the mechanism of soil water movement is lacking. Therefore, the present study explored soil water migration characteristics of two typical vegetation types [arbor land (AL) and shrub land (SL)] on the Loess Plateau during seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Seasonal freeze-thaw (FT) is a physical and geological natural phenomenon in which soil water undergoes more frequent phase changes during seasonal transitions due to cyclical changes in ambient temperature (Chou and Wang, 2021). It is widespread at mid to high latitudes and altitudes around the world and is particularly pronounced at high altitudes in northeast and northwest China (Bo et al, 2021;Huang et al, 2021). As an abiotic stress in soils (Cheng and Wu, 2007), FT first occurs in the topsoil and gradually extends to the subsoil (Liang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seasonal freeze-thaw (FT) is a physical and geological natural phenomenon in which soil water undergoes more frequent phase changes during seasonal transitions due to cyclical changes in ambient temperature (Chou and Wang, 2021). It is widespread at mid to high latitudes and altitudes around the world and is particularly pronounced at high altitudes in northeast and northwest China (Bo et al, 2021;Huang et al, 2021). As an abiotic stress in soils (Cheng and Wu, 2007), FT first occurs in the topsoil and gradually extends to the subsoil (Liang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This process has a potentially important impact on the carbon cycle of the soil (Guo et al, 2018;Huang et al, 2021). Vegetation plays an important role in the terrestrial carbon cycle (Malcolm et al, 2009;Wilkinson and Sherratt, 2016), but seasonal FT processes affect soil moisture distribution and directly influence vegetation growth activity (Bo et al, 2021). Studies have shown differences in the buffering effect of vegetation types on soil FT phenomena (Xiao et al, 2019;Bo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slope ecological restoration is an important measure for the construction of Nature-Enriched-Attributes-Coordinated-Watershed (Yan et al, 2017;. On the one hand, it directly affects vertical hydrological processes such as the atmospheric water vapor flux (Fathizadeh et al, 2017;Ghimire et al, 2017;Liu J. et al, 2018b), soil water movement (Wu et al, 2017;Huang et al, 2017;Yu et al, 2018;Bo et al, 2021;Xu M. et al, 2021), and evapotranspiration (Li et al, 2016;Wang et al, 2018). On the other hand, the canopy structure and community succession of vegetation indirectly affect the horizontal hydrological processes such as runoff generation and confluence on the slope (Amenu and Kumar, 2008;Yang et al, 2010;Dong et al, 2021) by changing the underlying surface conditions and the surface roughness.…”
Section: Introductionmentioning
confidence: 99%